2016
DOI: 10.13189/ujer.2016.041007
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Plyometric Education Trainings on Balance and Some Psychomotor Characteristics of School Handball Team

Abstract: This study aims to search the effects of plyometric education trainings which was applied for 10-week on static-dynamic balance and some psychomotor characteristics of students who were been handball team of school. The female students-players (N=16) who are in age 14,57±0,92 years. All student have got 3,66±0,63 years sport experience. Plyometric education trainings were performed twice a week for 10-week in the trainings of school handball team. Parameters such as body weight, height, vertical jump, standing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…From 6108 records initially identified through database searching, 14 JT studies 10,24,35,36,5160 conducted with handball players were found (Figure 1). However, from these, only five studies 10,24,35,59,60 incorporated a randomisation-controlled approach, and provided mean and standard deviation post-intervention data for the main outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…From 6108 records initially identified through database searching, 14 JT studies 10,24,35,36,5160 conducted with handball players were found (Figure 1). However, from these, only five studies 10,24,35,59,60 incorporated a randomisation-controlled approach, and provided mean and standard deviation post-intervention data for the main outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various exercise types, balance training and neuromuscular training (Eisen et al, 2010; Kang et al, 2013; Verhagen et al, 2005; Matin et al, 2014) were most commonly incorporated, followed by plyometric exercises and core stability training (Asadi et al, 2015; Karadenizli, 2016a, 2016b; Lust et al, 2009; Sato and Mokha, 2009). …”
Section: The Influence Of Balance Training On Balance In Various Spormentioning
confidence: 99%
“…In line with studies based on adult players, research with children has tend to relate to general motor skills e.g. Ingebrigsten & Jeffreys (2012); Ingebrigsten, Rodahl & Jeffreys, (2013); Zhunisbek et al, (2016); Broderick & Newell (1999); Karadenizli (2016); Kayapinar et al, (2015). Only a few studies have been conducted to consider effect of handball on improving motor skills in children, albeit tenuously, as it was mainly a physical characteristics study (Ion, 2015;Juhász et al, 2016;.…”
Section: Handball Specific Researchmentioning
confidence: 72%